The Tudors - Hull, Robert; Edited by Hook, Jason (England Wayland, 1997)
This book contains lively text which talks about Tudor history, artefacts and inventions. It has exciting colour photographs and covers a wide range of heritage themes.
Include Color Illustrations, Glossary and Index
Keywords: Great Britain -- Manners and customs -- England